(untitled) (Revista Innova Educación, 2023)
The development of artificial intelligence applications is raising alarms in the educational and professional community. Its potential to paraphrase or write texts make it very tempting to commit dishonest actions. Being a relatively current topic, there are no works that investigate the frequency and uses that students give to these tools in the educational field. The objective of this work was to explore the frequency and perceptions of use of this type of software in high school students of an educational institution. The research was non-experimental and of an exploratory-descriptive nature. The sample consisted of 83 high school students. The survey was used as techniques and the questionnaire as instruments. The results show that more than 62.9% of the students have used these tools to paraphrase and 4.8% to write complete essays, during the course. Most of them positively perceive their use, depending on different factors, but especially their lack of knowledge of what plagiarism is, as well as their poor academic writing skills. More in-depth studies are required to investigate the real frequency of this problem and how to prevent or detect it.